Histopathological profile of ovarian tumors in a tertiary care center- a descriptive study - V., Anitha Pallikkara; Ali, Shameem K. Ummer (International Journal of Research in Medical Sciences, 2021)
Background: Ovarian neoplasms are a heterogeneous group of tumors with varied clinical, morphological and histological features. Ovarian cancer accounts for about 3% of all cancer in females and is the 5th most common cause of death due to cancer because most ovarian tumors spread beyond ovary by the time of diagnosis. The objective of the study was to document the histological pattern and prevalence of ovarian tumors in specimens received at department of pathology government medical college Alappuzha. Methods: This was a prospective study of 18 months duration which comprised of 245 cases of ovariectomy and ovariotomy specimens received in the department of pathology, govt. T.D medical college Alappuzha, Kerala. After detailed and thorough gross examination of the specimens, bits from representative areas were routinely processed and stained with H and E. Tumors were classified as per WHO classification. Appropriate immunohistochemical studies were performed wherever required. Results: Out of 245 cases studied, majority were benign tumors (78.36%), followed by malignant tumors (15. 11%). Borderline tumors comprised (6.53%) of the total cases. Age groups studied ranged from 11-70 years. Epithelial tumors were the most common (76.32%) followed by germ cell tumors (17.55%), sex cord stromal tumors (5.03%) and carcinoma arising in germ cell tumors (0.81%). Serous cystadenoma was found to be the commonest benign tumor and serous cystadenocarcinoma was the commonest malignant ovarian neoplasm. Conclusions: Surface epithelial tumors were the most common ovarian tumors. The maximum number of tumors were noted in the age group 21-40 years. Malignant tumors were common above 40 years.